Gender and forestry: integrating local knowledge into environmental planning and management. (12th May 2004) - Martin, Adrian; Lemon, Mark
This paper demonstrates the importance of local knowledge to processes of rural development that involve changes to resource management regimes. The argument reveals that the cultural and economic contexts within which new policies are implemented can lead to unpredictable and unintended impacts that can contradict the objectives of environmental protection initiatives. Whilst local complexities make it impossible to predict all possible outcomes, planners and managers can nonetheless work with local knowledge in order to tailor initiatives to local contexts. The challenge is to both acquire and employ local cultural and economic feedback. These findings are conveyed through a consideration of headloading (the carrying and marketing of fuelwood) arid its relationship to forest management in the Western Ghats of Karnataka, South India. The data arc derived from six months of fieldwork during which six villages were studied. For the purposes of this paper, a case study of one village, Thaligadde, is employed.